Implementasi Sistem Pengenalan Wajah dengan Integrasi Firebase untuk Manajemen Kehadiran Real-Time - Syamjovanka, Revelin Putri; Citra Firdausi, Putri Aulia; Ana, Vika Rafi; Sari, Anggraini Puspita (UNIVERSITAS SERAMBI MEKKAH, 2024)
In the era of digitalization of education, administrative efficiency is the main focus of educational institutions to improve services. This research examines the application of a facial recognition system as a solution for updating the student attendance system at the University Pembangunan Nasional “Veteran” Jawa Timur. The manual methods currently used were identified as the main cause of inefficiencies and inaccuracies. Through Firebase integration, this system is implemented to enable real-time attendance management. Tests carried out on the University Pembangunan Nasional “Veteran” Jawa Timur (UPN Jatim) campus showed significant improvements in managing student attendance. The results show that this system provides an effective and efficient solution to administrative problems, with high accuracy and significant time reduction in the student attendance process.